A corpus-based approach to frame ‘COVID-19 vaccination’ in Malaysian English newspapers - Norasyikin Abdul Malik; Mohamad Syafiq Ya Shak; Nurul Ain Hasni (Penerbit Universiti Kebangsaan Malaysia, 2022)
Most studies on COVID-19 have been massively dedicated on how the disease was framed in the newspaper, its psychological effects, and its message or content disinformation. Research on the COVID-19 vaccination in newspapers and its acceptance among the masses is still quite scarce. The study adopted a corpus approach that involves wordlist, keyword list, collocates, and concordance analysis to analyse how ‘COVID-19 vaccination’ was framed in a focused and specialised English Malaysian newspapers corpus. #Lanscbox 5.0 corpus tool was employed in conducting the empirical analysis. The empirical analysis revealed that ‘COVID-19 vaccination’ was positively framed in different ways in the newspaper. The analysis of collocates and concordance lines revealed that the news reports mainly used Solution-oriented Frame which highlighted the Malaysian government’s effort in combating the pandemic. The newspaper was also found to use Mathematical frame in the effort to convince the public with regards to the updates and statistics of vaccine takers. Nevertheless, the results also revealed the usage of sensational phrases that framed the COVID-19 vaccination negatively. These findings can enlighten newspaper practitioners on what should be done and avoided in framing such an issue in their writings as well as how the public will perceive it.